Organizational Commitment and Job Satisfaction: Job Stress as Mediation - All Hidayat; Ririn Handayani; Adolf Bastian (SAINS ORGANISASI, 2022)
This study aims to see how Organizational Commitment and Job Satisfaction: Stress as a Mediation on Members of the Rokan Hilir Police. In addition, this study will also look at the interaction of the two variables. This type of research is explanatory research. The population is members of the Rokan Hilir Police Station, totaling 93 people. Data analysis in this study using SEM-PLS. Based on the data processing, it was found that there was a positive and significant relationship between organizational commitment and job satisfaction of the members of the Criminal Investigation Unit of the Rokan Hilir Police. The findings of this study are that work stress has a negative and significant effect on job satisfaction of the members of the Criminal Investigation Unit of the Rokan Hilir Police. Because the higher the job stress, it tends to reduce job satisfaction. The limitation of this study is the lack of population size used. So it is suggested to further researchers to continue this research by developing the population so that the results can be generalized.